Future visions of the functionality of the industrial product and its communicative capacity - Barakat, r. Mustafa Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
Future research and studies have taken place in all fields of knowledge and all the scientific and humanitarian disciplines and to the study of the importance of reaching to know the real and effective communication between the industrial and the receiver product language through various means of communication that it contains product design and of functional communication and formal and aesthetic and technical gave way to show diversity in design trends industrial products, according to career and aesthetic performance value addition to the raw material specifications, organization and composition of the design and the ability of communication, where the design innovations in industrial achievements emerged through the introduction of changes in the morphological and functional systems in the building design has been associated with the function of the industrial product and the accompanying technical evolution of the material is a necessity in Browning concept of the design. All of these influences combined together and the lack of field of art in the field of industrial design for such a study, which may set the foundations for future visions for the job of communication research. The study of this will pave the way for designers of industrial achievement has to be implemented according to the pillars that help in creating a future vision for the job communicative expected to occur in the future.